Finite Element Analysis of Proximal Femoral Bionic Nail (PFBN), Proximal Femoral Nail Antirotation and InterTan for Treatment of Reverse Obliquity Intertrochanteric Fractures - Chen Xiong; Lijia Zhang; Yanhua Wang; Xiaomeng Zhang; Xiaofeng Chen; Kai Yu; Yichong Zhang; Huijuan Fu; Zhentao Ding; Dianying Zhang (Orthopaedic Surgery, 2025)
ABSTRACT Objective Reverse obliquity intertrochanteric fracture is an unstable type of fracture. Current guidelines recommend intramedullary fixation, but there are still complications such as screw removal, hip varus, nail withdrawal, and nail fracture. The objective of this study was to use finite element analysis to compare the biomechanical properties of the novel proximal femoral bionic nail (PFBN), proximal femoral nail antirotation (PFNA), and combined compression interlocking intramedullary nail (InterTan) in the treatment of reverse obliquity intertrochanteric fractures (AO/OTA 31‐A3.1). Methods The three‐dimensional models of PFBN, PFNA, InterTan, and the A3.1 type intertrochanteric fracture model were established by using modeling software such as Mimics and Unigraphics. Different force loads were implemented using ANSYS software to compare finite element biomechanical parameters, such as maximum stress in the implant and maximum stress and displacement at the proximal femur. Results In this finite element study, we found that the distribution trend of maximum femoral stress and displacement in the femoral models of the three internal fixation groups was similar, but the maximum stress and maximum displacement were the lowest in the PFBN group, and the maximum stress of the internal fixation implant in the PFBN group was lower than that in the PFNA group and the InterTan group. The maximum stress and displacement of the femur in the PFNA group were 403.71 MPa and 14.274 mm, respectively, the maximum stress and displacement in the InterTan group were 362.72 MPa and 10.678 mm, and the maximum stress and displacement in the PFBN group were 186.23 MPa and 9.7068 mm. In the internal fixation implant model, the maximum stress of the PFNA group was 1445 MPa, the maximum stress of the InterTan group was 919.62 MPa, and the maximum stress of the PFBN group was the lowest, at 911.77 MPa. Conclusion Compared to PFNA and InterTan, PFBN designed by the “lever – reconstruction – balance” hypothesis can provide better biomechanical stability. It is a feasible choice for the future treatment of reverse intertrochanteric fracture, and additional clinical studies are required to substantiate its efficacy.